Dying at home or in the hospital? An observational study in German general practice. (2nd January 2016) - Gágyor, Ildikó; Himmel, Wolfgang; Pierau, Andrea; Chenot, Jean-François
ABSTRACT: Background Although determinants of place of death have been investigated in several studies, there is a lack of knowledge on factors associated with dying at home from the general practice perspective. Objectives To identify factors associated with dying at home for patients in German general practice. Methods In a retrospective study, general practitioners of 30 general practices were asked to provide data for all patients aged 18 years or older who died within the last 12 months, using a self-developed questionnaire. 'Dying in hospital' was defined as dying in hospital or hospice and 'dying at home' as dying at one's usual residence including the nursing home. Multiple logistic regression analyses were used to determine factors associated with 'dying at home'; odds ratios (ORs) and their 95% confidence intervals (CI) were calculated as measures of effect size. Results Of 439 deceased patients, 52.2% died at home, and 47.8% died in hospital or hospice. Determinants for dying at home were patients' care in the last 48 hours of life by family members (OR: 7.8, 95% CI: 3.4–18.0), by general practitioners (GPs) (OR: 7.3, 4.2–12.9) and living in a nursing home (OR: 3.8, 1.7–8.3). In the adjusted model, low comorbidity was positively associated (OR: 3.2, 1.4–7.0), and low functional health status (Karnofsky performance status) was negatively associated with dying at home (OR: 0.3, 0.1–0.7). Conclusion Apart from patient-related factors such as comorbidity and health status, care by family members and GPs respectively, were determinants of dying at home.